Pelatihan Pembuatan Serta Pemasaran Olahan Kulit Manggis Menjadi Cookies Melalui Instagram Kepada Masyarakat Desa Ponggang - Alma Izzatis Sullami; Shafa Rahmah; Via Nur Setyani; Tabrani Sjafrizal (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Mangosteen fruit is one of the natural resources owned by Ponggang Village, Serangpanjang District, Subang Regency. Many benefits can be obtained from eating the mangosteen fruit, especially the skin of the fruit. The harvest from the mangosteen fruit will be marketed by the mangosteen farmers. But before that, the mangosteens to be sold must go through a sorting stage to see which mangosteens are fit for sale. If there are mangosteen fruit that is not suitable for sale, then the mangosteen fruit becomes unused waste. From these problems, community service was carried out regarding training in the manufacture and marketing of processed mangosteen rind into cookies through Instagram media. The purpose of this training is so that the mangosteen rind is not wasted and can be processed into food that can add to the economy of the local community. The method used in this community service activity is socialization and training on how to make processed cookies from mangosteen rind. The results of the community service activities were that this training achieved several targets, namely mangosteen warehouse owners, PKK mothers, farmers and MSME owners. After the training on making cookies from fruit peels, marketing was carried out through Instagram social media so that it could be marketed widely.